Leaching characteristics of heavy metals in tailings and their simultaneous immobilization with triethylenetetramine functioned montmorillonite (TETA-Mt) against simulated acid rain. (November 2020) - Huang, Zhiyan; Jiang, Lu; Wu, Pingxiao; Dang, Zhi; Zhu, Nengwu; Liu, Zehua; Luo, Hanjin
Abstract: For further understanding leaching characteristics of heavy metals in tailings and better immobilization on heavy metals against acid rain, batch experiments were conducted. The leaching results of Cu(II), Zn(II), Cd(II) and Mn(II) can be well fit by second-order kinetics equation, and Pb(II) can be well fit by two-constant equation. The leaching intensity of heavy metals in tailings was ranged as: Mn(II)> Cu(II)> Cd(II)> Zn(II)> Pb(II). Triethylenetetramine functioned montmorillonite (TETA-Mt) was successfully synthesized and can obtain simultaneous immobilization effect compared with Mt and TETA, and immobilization rates on Cu(II), Cd(II), Mn(II) and Zn(II) can reach above 90%, the immobilization rate on Pb(II) can reach more than 75%. The mechanisms for efficient immobilization of heavy metals on TETA-Mt included buffering and adsorption abilities. The mechanism for TETA-Mt adsorption of heavy metals included physical absorption, chelation and chemical sedimentation. The results showed that TETA-Mt can be applied to effective immobilization of heavy metals in tailings and efficient remediation of acid mine drainage (AMD) in acid rain area. Graphical abstract: Image 1 Highlights: The leaching intensity of heavy metals in tailings was ranged as: Mn(II)> Cu(II)> Cd(II)> Zn(II)> Pb(II). Triethylenetetramine functioned montmorillonite (TETA-Mt) was successfully prepared. Simultaneous immobilization of Cd(II), Cu(II), Pb(II), Zn(II) and Mn(II) with TETA-Mt. TETA-Mt had enhanced buffering and adsorption capacity.